KEPEMIMPINAN KEPALA SDN 01 BATANG HARI - Titin Amiati (UNISAN JURNAL, 2024)
School education is organized to continue and expand basic education and prepare students to become members of the community who can have reciprocal relationships with the environment, socio-culture and can develop more skills in the world of work or higher education. The purpose of this study was to determine the extent of the implementation of the school principal’s situational leadership style and to determine the supporting and inhibiting factors for the implementation of the principal’s situational leadership style at SDN2 Tanjung Ratu, South Lampung. This study uses a qualitative method. The subject of the research is the principal, the data is collected by using in-depth interview techniques with informants, observation and documentation. Based on the results and analysis of the findings of the implementation of the situational leadership style of the principal of SDN 2 Tanjung Ratu, South Lampung. The success of an organization will not be separated from the various factors that support it. Situational leadership style can affect the performance of teachers and employees. Leadership is the process of being able to lead. Leaders have to do something. leaders must tell teachers and employees to take action. Leaders inform teachers in a variety of ways, such as using legitimate authority, creating models (setting examples), setting goals, rewarding and legalizing, restructuring the organization, and communicating vision.